A Rare Pediatric Case of Lacrimal Gland Pleomorphic Adenoma. Issue 9 (September 2019) - Bryant, Justin R.; Mantilla-Rivas, Esperanza; Manrique, Monica; Keating, Robert F.; Nik, Narieman A.; Oh, Albert K.; Rogers, Gary F.
Abstract : Summary: Pleomorphic adenoma of the lacrimal gland is a rare benign finding in adults, and extremely uncommon in children. These tumors often present with increased propotosis or hypoglobus, and they invariably require operative excision. While many of these lesions can be removed through a subcranial or transorbital exposure, larger and more posterior tumors occasionally necessitate an intracranial approach. This report describes a large lacrimal gland pleomorphic adenoma in a 16 year-old patient that required use of an expansive intracranial exposure to ensure complete excision including the capsule. We contrast this case and its management to other pediatric cases described in the literature.